Production of leading charged particles and leading charged-particle jets at small transverse momenta in pp collisions at root s=8 TeV - (:unkn) unknown (AMER PHYSICAL SOC, 2015)
The per-event yield of the highest transverse momentum charged particle and charged-particle jet, integrated above a given p(T)(min) threshold starting at p(T)(min) = 0.8 and 1 GeV, respectively, is studied in pp collisions at root s = 8 TeV. The particles and the jets are measured in the pseudorapidity ranges vertical bar n vertical bar < 2.4 and 1.9, respectively. The data are sensitive to the momentum scale at which parton densities saturate in the proton, to multiple partonic interactions, and to other key aspects of the transition between the soft and hard QCD regimes in hadronic collisions.